Physical Activity, Physical Fitness, Resilience, And Socio-Emotional Strength: A Correlational Study Of High School Students (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to examine the relationship between physical activity, physical fitness, resilience, and social-emotional skills in senior high school (SMA) students. This study used a quantitative approach with a correlational design. The study sample involved 98 students of grades X and XI of SMA Negeri 1, Teluk Belengkong District, selected using a purposive sampling technique. Data were collected through a questionnaire adapted from The Physical Activity Questionnaire for Adolescents (PAQ-A), physical fitness measurements using the Multistage Fitness Test (MFT) or Bleep Test, adapted questionnaires from the resilience scales for adolescents, psychological symptoms, and clinical status in adolescents, and adapted questionnaires from the Development of Social Emotional Competency Scale for Students. Data analysis used Pearson correlation and multiple linear regression. The results of the study showed a significant relationship between physical activity and physical fitness (r = 0.419, p < 0.05), physical activity and resilience (r = 0.298, p < 0.05), physical activity and social emotional (r = 0.295, p < 0.05), physical fitness and resilience (r = 0.235, p < 0.05), physical fitness and social emotional (r = 0.212, p < 0.05), and resilience and social emotional (r = 0.423, p < 0.05). These findings indicate the importance of physical activity and physical fitness in supporting the resilience and social-emotional emotional of high school students.